The Influence of School Leadership and The School Environment on The Performance of Teachers at Secondary School São Francisco De Assis, in The 2022 School Year - Sancha Francisca da Conceição; Agostinho dos Santos Gonçalves; Maria da Costa (International Journal of Psychology and Health Science, 2023)
In this research, the researcher examines the performance of teachers using the independent variables are school leadership and school environment. The population of this study were teachers who were related to school leadership and the school environment was made up of structures or sectors withinterest in the work of teachers 68 people. The data collection method used is the questionnaire method. The technique to analyze is multiple linear regression where the results show y = a+ b1.X2 + b2.x2 + e, the multiple linear regression result y = 11.447 + 0.026X1 + 0.451 X2) have a fixed value of 11,447 based on hypothesis testing for coefisien regresses school leadership (X1) with the Tcount value is 0.256 and the Ttable value is 1.668 with confidence level 5% real level 95% however the Tcount value lower than Ttable is 0.256< 1.668. This explains why the school leadership variable (X1) does not have a positive and significant effect on teacher performance (X2) based on hypothesis testing for coefisien returns school environment (X1) with the value Tcount is 4.198 and the value Ttable is 1.668 with confidence level 95% real level 5%however the value Tcount lower than Ttable is 4.198< 1.668. This explains that the School Environment variable (X2) has a positive and significant effect on teachers' performance (Y). While simultaneously obtained Fcount is 9,196 total (2.354) and a significance level of 0.000 < 5% Based on this study, it can be concluded that the research hypothesis is that there is a significant influence between School Leadership and School Environment on teachers' performance.